2019
DOI: 10.1136/jech-2018-212049
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance and education: major contributors to oral health inequalities in Colombia

Abstract: BackgroundHealth inequalities, including inequalities in oral health, are problems of social injustice worldwide. Evidence on this issue from low-income and middle-income countries is still needed. We aimed to examine the relationship between oral health and different dimensions of socioeconomic position (SEP) in Colombia, a very unequal society emerging from a long-lasting internal armed conflict.MethodsUsing data from the last Colombian Oral Health Survey (2014), we analysed inequalities in severe untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
4
8
0
4
Order By: Relevance
“…The statistical analyses (logistic regression and SEM) revealed that health insurance and discrimination are relevant factors accounting for a portion of the association between SEP and oral health. This finding extends previous studies on the role of health insurance [ 52 55 ] and discrimination [ 24 , 25 , 46 – 49 , 51 , 56 ] as well as explaining (oral) health inequalities across countries.…”
Section: Discussionsupporting
confidence: 89%
“…The statistical analyses (logistic regression and SEM) revealed that health insurance and discrimination are relevant factors accounting for a portion of the association between SEP and oral health. This finding extends previous studies on the role of health insurance [ 52 55 ] and discrimination [ 24 , 25 , 46 – 49 , 51 , 56 ] as well as explaining (oral) health inequalities across countries.…”
Section: Discussionsupporting
confidence: 89%
“…51,63 A national-level study done in Colombia that looked at the association of different socioeconomic-position dimensions and oral health found that those who lacked national-health insurance and those with lower education levels showed the highest oral health problems. 64 Cross-sectional studies conducted in Chile in 2-4-year-old and 4-year-old children, 65 as well as in Colombia in 8-71-month-old children, 46 and in Mexico in 3-6-year-old children 61 showed that older age was associated with an increased relevance and severity of caries.…”
Section: Socioeconomic and Demographic Factors In Laccmentioning
confidence: 99%
“…The health insurance scheme does not seem to help address health inequalities, which has also been emphasized in other analyses with Colombian data [36,[44][45][46]. Systematic inequalities exist, with those uninsured or in the subsidized scheme having higher neonatal mortality rates [47], shorter gastric cancer survival rates [36], longer delays in tuberculosis diagnosis [45], less frequent use of preventive services [48,49], more barriers to accessing health care when needed [50] and poorer oral health [37]. This evidence, together with our findings, suggests that the Colombian health care system urgently needs to shift towards universal coverage and a structural redesign to address these high levels of fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves a proportion of the population (6% in our data) as uninsured, i.e., those who are not in formal employment or able to pay a monthly fee and are not considered 'poor' based on the means test. Although not a direct measure of SEP, health insurance status has been used as a proxy for socioeconomic circumstances in previous analyses of health inequalities in Colombia [36,37] due to the abovementioned features of the different schemes.…”
Section: Plos Onementioning
confidence: 99%